Invited Commentary: Use of Arsenical Skin Lesions to Predict Risk of Internal Cancer—Implications for Prevention and Future Research - Ahsan, Habibul (Oxford University Press, 2013)
Arsenic exposure affects millions of people worldwide, causing substantial mortality and morbidity from cancers and cardiovascular and respiratory diseases. An article in the current issue (Am J Epidemiol. 2013;177(3):202–212) reports that classic dermatological manifestations, typically associated with chronic arsenic exposure, are predictive of internal cancers among Taiwanese decades after the cessation of exposure. Specifically, the risk of lung and urothelial cancers was elevated, which was evident regardless of arsenic dose, smoking, and age. There was also an unexpected elevated risk of prostate cancer. Despite some methodological limitations, these findings underscore the need for assessing whether dermatological manifestations are also predictive of cardiovascular, respiratory, and other arsenic-related, long-term health consequences. Given the emerging evidence of arsenic exposure from dietary sources beyond contaminated drinking water and occupational and environmental settings, and also because the vast majority of diseases and deaths among exposed populations do not show classic dermatological manifestations, larger and more comprehensive investigations of the health effects of arsenic exposure, especially at lower doses, are needed. In parallel, because the risk of known arsenic-related health outcomes remains elevated decades after exposure cessation, research toward identification of early clinical and biological markers of long-term risk as well as avenues for prevention, in addition to policy actions for exposure reductions, is warranted.